Syntheses of novel 1, 5‐benzodiazepine derivatives: Crystal structures, spectroscopic characterizations, Hirshfeld surface analyses, molecular docking studies, DFT calculations, corrosion inhibition anticipation, and antibacterial activities. (27th October 2020) - El Ghayati, Lhoussaine; Sert, Yusuf; Sebbar, Nada Kheira; Ramli, Youssef; Ahabchane, Noureddine Hamou; Talbaoui, Ahmed; Mague, Joel T.; El Ibrahimi, Brahim; Taha, Mohamed Labd; Essassi, El Mokhtar; Al‐Zaqri, Nabil; Alsalme, Ali
Abstract: A series of newly pyrazolo‐1, 5‐benzodiazepine derivatives (5 ‐7 ) was performed and characterized by using 1 H, 13 C‐NMR spectroscopic measurements. The molecular and crystal structures of two compounds 2 and 7 have also been further examined by single‐crystal X‐ray crystallography showing that the alkyl groups are beard by sulfur atom and to pyrazolic nitrogen atom in position 2 and not in position 1 of the tricyclic compounds as described in the literature. In addition, through Hirshfeld surface analysis, molecular docking studies, and DFT calculations, the closest contact between the active atoms of the compound can be determined. Also, the Monte Carlo simulations outcomes show that compounds 2 and 7 can be considered as a good acidic corrosion inhibitor for the aluminum metal, while emphasizing that the compound 7 provides enhanced prevention. Finally, compounds 1 to 7 were evaluated for their antibacterial activity against Gram‐positive and Gram‐negative microbial strains such as Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus . The results obtained demonstrated the antibacterial activity of compounds 1 to 7 tested using the minimal inhibitory concentration. Abstract :